Odorant receptors at the growth cone are coupled to localized cAMP and Ca2+ increases. - Maritan, M; Monaco, G; Zamparo, I; Zaccolo, M; Pozzan, T; Lodovichi, C (2009)
A distinctive feature in the topographic organization of the olfactory system in mammals is the dual function of the odorant receptor (OR): it detects odors in the nasal epithelium and plays an instructive role in the axonal convergence of olfactory sensory neurons (OSN) into the olfactory bulb (OB). The latter function is supported by genetic experiments and by the expression of the OR not only on the cilia, but also on the axon termini of the OSN. The signaling pathway coupled to the OR on the cilia is well known and is recognized to involve cAMP and Ca(2+), whereas, until now, nothing was known on the functional characteristics of the OR on the axon termini-growth cone. Here, by analyzing the spatiotemporal dynamics of cAMP and Ca(2+) in living OSN in vitro and in situ, we found that the OR at the growth cone is capable of binding odors and is coupled to cAMP synthesis and Ca(2+) influx through cyclic nucleotide gated (CNG) channels. Furthermore we found that selective odor activation of the OR on the growth cone is followed by nuclear translocation of protein kinase A catalytic subunit. These results define the functional properties of the OR on the growth cone and suggest a potential role of OR activation in axonal convergence and sensory map formation.